2008
DOI: 10.1016/j.brainres.2008.03.070
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of TNFα on nerve fiber formation from ventral mesencephalic organotypic tissue cultures

Abstract: Tumor necrosis factor alpha (TNFα) is toxic to dopamine neurons and increased levels of TNFα are observed in Parkinson's disease. Dopamine nerve fiber outgrowth in organotypic cultures of fetal ventral mesencephalon occurs in two waves. The early appearing nerve fibers are formed in the absence of astroglia, while migrating astrocytes guide the late appearing dopamine nerve fibers. TNFα (40 ng/ml) was added to the medium of organotypic ventral mesencephalic tissue cultures between days 4-7 or 11-14. The cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…Previously, we and others have demonstrated in organotypic dorsal root ganglia cultures that TNF-alpha reduces neurite outgrowth in the peripheral nervous system (15,24). In organotypic mesencephalic brain slices TNF-alpha has been shown to support glia-dependent neurite growth (28). In the present study we have demonstrated that TNF-alpha increases neurite outgrowth in brain slices by nearly 45%, thus, at a level comparable with the stimulatory effects of hypothermia.…”
Section: Discussionsupporting
confidence: 76%
“…Previously, we and others have demonstrated in organotypic dorsal root ganglia cultures that TNF-alpha reduces neurite outgrowth in the peripheral nervous system (15,24). In organotypic mesencephalic brain slices TNF-alpha has been shown to support glia-dependent neurite growth (28). In the present study we have demonstrated that TNF-alpha increases neurite outgrowth in brain slices by nearly 45%, thus, at a level comparable with the stimulatory effects of hypothermia.…”
Section: Discussionsupporting
confidence: 76%
“…Conversely, the deficiency of BDNF or NGF is believed to be a cause or a trigger of neurodegeneration [43,44]. Thus, NGF and BDNF, or their receptor agonists, have been used to treat AD and other neurodegenerative diseases [12,45,46]. Dr O’Banion’s team has recently demonstrated that chronic over expression of IL-1 impairs adult hippocampal neurogenesis in the above mentioned mouse model [47].…”
Section: Discussionmentioning
confidence: 99%
“…Even though many studies have reported that increased IL-1 release contributes to neurodegeneration in both acute and chronic brain conditions, findings from acute ischemia, stroke and brain injuries show that the release of IL-1 and other pro-inflammatory cytokines, such as TNF-α, may protect neurons [8-12]. However, many studies have demonstrated that blocking IL-1 or reducing inflammation could reduce neuron death and symptoms of disability as well as save patients’ lives [13].…”
Section: Introductionmentioning
confidence: 99%
“…This suggestion is strengthened by the fact that the length of these neurites was comparable, independent of treatment. Interestingly, to date, nothing but time in culture has improved the length of these non‐glial‐associated nerve fibers as long as they are present (af Bjerkén et al, 2007; Marschinke and Strömberg, 2008). Thus, regarding studies on effects of for instance neurotrophic factors on cultured dopamine neurons, survival time is then an important factor, since the non‐glial‐ and the glial‐associated growths might be affected differently.…”
Section: Discussionmentioning
confidence: 99%